Polymer solid electrolyte and all-solid-state battery containing same
By employing polyhedral oligomeric silsesquioxane (POSS) with crosslinkable functional groups and lithium salts, the challenges of achieving high ionic conductivity and safety in polymer solid electrolytes are addressed, resulting in improved performance for all-solid-state batteries.
Patent Information
- Application Number
- JP2024541239
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-25
- Filing Date
- 2023-10-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-10-20
AI Technical Summary
Conventional polymer solid electrolytes face limitations in achieving both high ionic conductivity and safety due to their high crystallinity, making it difficult to produce effective solid electrolytes for lithium secondary batteries.
The use of polyhedral oligomeric silsesquioxane (POSS) containing crosslinkable functional groups and lithium salts in a curing process to form a crosslinked structure, enhancing both safety and ionic conductivity in solid polymer electrolytes.
The crosslinked structure formed by POSS and lithium salts improves the safety and ionic conductivity of polymer solid electrolytes, preventing leakage and volatilization while allowing for efficient ion movement, suitable for use in all-solid-state batteries.
Smart Images

Figure 2025502136000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0138008 dated October 25, 2022, Korean Patent Application No. 10-2022-0138012 dated October 25, 2022, and Korean Patent Application No. 10-2022-0137997 dated October 25, 2022, and all contents disclosed in the documents of those Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a polymer solid electrolyte and an all-solid-state battery containing the same. [Background technology]
[0003] Lithium secondary batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, and if the separator is damaged by deformation or external impact, a short circuit can occur, which can lead to risks such as overheating and explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium secondary batteries is a very important issue.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of improved battery safety and the prevention of electrolyte leakage, which improves battery reliability and makes it easier to manufacture thin batteries. In addition, because lithium metal can be used as the negative electrode, the energy density can be improved, and it is expected to be used in small secondary batteries as well as high-capacity secondary batteries for electric vehicles, and is attracting attention as a next-generation battery.
[0005] Among solid electrolytes, polymeric solid electrolytes may be made from ion-conductive polymer materials, and hybrid materials in which polymeric and inorganic materials are mixed have also been proposed. The inorganic material may be an inorganic material such as an oxide or sulfide.
[0006] Such conventional polymer solid electrolytes are manufactured through a process of forming a coating film and then drying it at a high temperature. However, the conventional manufacturing technology for polymer solid electrolytes has a limitation in that it is difficult to manufacture a polymer solid electrolyte with improved ionic conductivity due to the high crystallinity of crystalline polymers or semi-crystalline polymers.
[0007] Therefore, there is a continuing need for technological development of polymer solid electrolytes that simultaneously have the properties of safety and ionic conductivity. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 2017-0046995 Summary of the Invention [Problem to be solved by the invention]
[0009] As a result of extensive research to solve the above problems, the present inventors have confirmed that (A) the safety and ionic conductivity of a polymer solid electrolyte prepared by using a liquid phase polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) and a lithium salt as raw materials and subjecting the raw materials to a curing process are improved at the same time.
[0010] In addition, the present inventors have confirmed that the safety and ionic conductivity of the polymer solid electrolyte after the curing process are improved at the same time by using (B) polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) (CFG-POSS); liquid-phase polyhedral oligomeric silsesquioxane (polyethyleneglycol-polyhedral oligomeric silsesquioxane (POSS)); and lithium salt as raw materials.
[0011] In addition, the present inventors have confirmed that the safety and ionic conductivity of the polymer solid electrolyte are improved simultaneously after the curing process using liquid-phase polyhedral oligomeric silsesquioxane (POSS), a solid-phase cross-linking agent, and a lithium salt as raw materials.
[0012] Therefore, an object of the present invention is to provide a polymer solid electrolyte which is excellent in safety and ionic conductivity.
[0013] Another object of the present invention is to provide an all-solid-state battery including a solid polymer electrolyte having improved safety and ionic conductivity.
[0014] Another object of the present invention is to provide a battery module including the all-solid-state battery. [Means for solving the problem]
[0015] In order to achieve the above object, the present invention provides a polymer solid electrolyte comprising the following (A), (B) or (C): The polymer solid electrolyte containing the (A) or (B) has a crosslinked structure formed by crosslinking between the crosslinkable functional groups, The polymer solid electrolyte containing the (C) has a cross-linked structure formed by the solid-phase cross-linking agent, and the polymer solid electrolyte is provided as follows: (A) polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) and a lithium salt; (B) polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) (CFG-POSS); liquid-phase polyhedral oligomeric silsesquioxane (POSS); and a lithium salt; and (C) Polyhedral oligomeric silsesquioxane (POSS) in the liquid phase; a cross-linking agent in the solid phase; and a lithium salt.
[0016] In one embodiment of the present invention, the crosslinkable functional group of (A) may include one or more selected from the group consisting of glycidyl (GL) and acrylo (AC).
[0017] In one embodiment of the present invention, the (A) polyhedral oligomeric silsesquioxane containing a crosslinkable functional group may be contained in an amount of 50% by weight to 95% by weight based on the total weight of the polymer solid electrolyte.
[0018] In one embodiment of the present invention, the (A) lithium salt may be contained in an amount of 5 wt % to 50 wt % based on the total weight of the polymer solid electrolyte.
[0019] In one embodiment of the present invention, the crosslinkable functional group (CFG) of (B) may include one or more selected from the group consisting of glycidyl (GL), acrylo (AC), allyl (AL) and methacryl (MA).
[0020] In one embodiment of the present invention, the weight ratio (CFG-POSS:POSS) of the polyhedral oligomeric silsesquioxane containing a crosslinkable functional group (B) to the polyhedral oligomeric silsesquioxane (POSS) may be 0.05:1 to 1.5:1.
[0021] In one embodiment of the present invention, the (B) polyhedral oligomeric silsesquioxane (CFG-POSS) having a crosslinkable functional group may be contained in an amount of 20 wt % to 50 wt % based on the total weight of the polymer solid electrolyte.
[0022] In one embodiment of the present invention, the (B) polyhedral oligomeric silsesquioxane (POSS) may be contained in an amount of 20% by weight to 50% by weight based on the total weight of the polymer solid electrolyte.
[0023] In one embodiment of the present invention, the lithium salt (B) may be contained in an amount of 10% by weight to 40% by weight based on the total weight of the polymer solid electrolyte.
[0024] In one embodiment of the present invention, the solid-phase cross-linking agent (C) may include one or more selected from the group consisting of polyethylene glycol diacrylate (Poly(ethylene glycol) diacrylate (PEGDA)), polyethylene glycol dimethacrylate (PEGDMA) and polyethylene glycol divinyl ether (PEGDVE).
[0025] In one embodiment of the present invention, the liquid phase polyhedral oligomeric silsesquioxane (POSS) of (C) may be contained in an amount of 20 wt % to 60 wt % based on the total weight of the polymer solid electrolyte.
[0026] In one embodiment of the present invention, the solid-phase cross-linking agent (C) may be contained in an amount of 20% by weight to 60% by weight based on the total weight of the polymer solid electrolyte.
[0027] In one embodiment of the present invention, the lithium salt of (C) may be contained in an amount of 10% by weight to 30% by weight based on the total weight of the polymer solid electrolyte.
[0028] In one embodiment of the present invention, the polymer solid electrolyte may be in the form of a freestanding film.
[0029] In one embodiment of the present invention, the polymer solid electrolyte may further contain a liquid electrolyte.
[0030] The present invention also provides an all-solid-state battery comprising a solid polymer electrolyte.
[0031] In one embodiment of the present invention, the all-solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, and at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer may include the polymer solid electrolyte.
[0032] The present invention also provides a battery module including the all-solid-state battery. Effect of the Invention
[0033] The polymer solid electrolyte according to the present invention can prevent leakage and volatilization due to a crosslinked structure formed by polyhedral oligomeric silsesquioxane containing a crosslinkable functional group and / or a solid-phase crosslinking agent, and exhibits excellent effects in terms of safety and ionic conductivity. [Brief description of the drawings]
[0034] [Figure 1] FIG. 1 is a schematic diagram showing the internal structure of a polymer solid electrolyte (A) according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing the internal structure of a polymer solid electrolyte (B) according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing the internal structure of a polymer solid electrolyte (C) according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] In the following, the present invention will be described in further detail to aid in understanding the invention.
[0036] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0037] As used herein, the term "crosslinkable functional group" refers to a functional group that can form crosslinks between the functional groups in a three-dimensional network form to form a crosslinked structure.
[0038] The term "crosslinked structure" as used herein refers to a structure including a three-dimensional framework formed by crosslinking between functional groups contained in a liquid-phase polyhedral oligomeric silsesquioxane and / or a solid-phase crosslinking agent, and an internal space formed within the framework. The internal space may include a free volume.
[0039] Polymer solid electrolyte The present invention relates to a polymer solid electrolyte.
[0040] The polymer solid electrolyte according to the present invention is a polymer solid electrolyte comprising the following (A), (B) or (C): The polymer solid electrolyte containing the (A) or (B) has a cross-linked structure formed by cross-linking between the cross-linkable functional groups, The polymer solid electrolyte containing (C) has a cross-linked structure formed by the solid-phase cross-linking agent: (A) polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) and a lithium salt; (B) polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) (CFG-POSS); liquid-phase polyhedral oligomeric silsesquioxane (POSS); and a lithium salt; and (C) Polyhedral oligomeric silsesquioxane (POSS) in the liquid phase; a cross-linking agent in the solid phase; and a lithium salt.
[0041] Hereinafter, the polymer solid electrolytes containing the above-mentioned (A), (B) or (C) will be divided into polymer solid electrolyte (A), polymer solid electrolyte (B) and polymer solid electrolyte (C), respectively, and these polymer solid electrolytes will be described in more detail.
[0042] [Polymer solid electrolyte (A)] (1) Polymer solid electrolyte (A) The present invention relates to a polymer solid electrolyte (A).
[0043] The polymer solid electrolyte (A) according to the present invention includes polyhedral oligomeric silsesquioxane (POSS) (CFG-POSS) containing a crosslinkable functional group (CFG), and a lithium salt. The CGF-POSS is in a liquid phase at room temperature, and therefore in the raw material state, but in the polymer solid electrolyte, it shows a crosslinked structure due to crosslinking between the functional groups after heat treatment.
[0044] In addition, the polymer solid electrolyte has a cross-linked structure formed by cross-linking between the cross-linkable functional groups, and the lithium salt may be present in a dissociated state in a free volume, which is an internal space of the cross-linked structure.
[0045] The POSS itself has a cage shape. Since a cage is a three-dimensional structure including a free volume, it may be a type of three-dimensional network cross-linked structure. The cross-linkable functional group may be an end group bonded to an end of the POSS. A cross-linked structure including a free volume may be formed by cross-linking between the cross-linkable functional groups that are the end groups of the POSS. The cross-linked structure may also include the cage structure of the POSS itself.
[0046] In addition, the free volume can provide a space in which the solid electrolyte chains can move, thereby improving ionic conductivity.
[0047] In the present invention, the polyhedral oligomeric silsesquioxane (POSS) may be represented by the following Chemical Formula 1:
[0048] [ka]
[0049] In the above Chemical Formula 1, R are the same or different and are each independently selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4:
[0050] [ka]
[0051] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.
[0052] In addition, in the above chemical formulas 1-1 to 1-4, L1 to L5 are C1 to C10 alkylene groups, R1 to R4 are hydrogen, a hydroxyl group, or a C1 to C30 alkyl group, and m and n are the same or different and each independently an integer of 0 to 10.
[0053] In addition, in the above formula 1, R is selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group.
[0054] FIG. 1 is a schematic diagram showing the internal structure of a polymer solid electrolyte (A) according to one embodiment of the present invention.
[0055] 1, the polymer solid electrolyte (1) has a cross-linked structure formed by cross-linking between functional groups contained in a polyhedral oligomeric silsesquioxane (CFG-POSS) (10) containing a cross-linkable functional group, and an internal space contained in the cross-linked structure. In this case, the internal space may refer to a free volume. The lithium salt (30) may be contained in a dissociated state in the internal space.
[0056] The crosslinkable functional group is not particularly limited as long as it has a property of forming a crosslink by a curing process using heat or light. For example, the crosslinkable functional group may include one or more selected from the group consisting of glycidyl and acrylo. The glycidyl may be more advantageous for a crosslinked structure by crosslinking because it has a stronger tendency to bond with each other during heat treatment and / or light treatment. Preferably, the crosslink may be a bond formed by thermal crosslinking of glycidyl.
[0057] The strength of the cross-linking may affect the degree to which the polymer chains contained in the polymer solid electrolyte can move. Therefore, if the cross-linking is not bonded with an appropriate strength to allow the polymer chains to move, the solid electrolyte membrane cannot exhibit high ion conductivity while maintaining its strength. If the strength of the cross-linking is too high, the polymer chains may not move smoothly and it may be difficult to secure space for ions to move, resulting in low ion conductivity. On the other hand, if the strength of the cross-linking is too low, the processability may be reduced during the manufacture of the all-solid-state battery, and leakage may occur.
[0058] In addition, the polyhedral oligomeric silsesquioxane (CFG-POSS) containing a crosslinkable functional group may be included in an amount of 50 wt% to 95 wt% based on the total weight of the polymer solid electrolyte, specifically, 50 wt% or more, 60 wt% or more, or 65 wt% or more, or 91 wt% or less, 93 wt% or less, or 95 wt% or less. If the content of the CFG-POSS is less than 50 wt%, a polymer solid electrolyte cannot be formed, and if it exceeds 95 wt%, the ion conductivity increases, but the strength decreases or it may become liquid phase, making it difficult to form a solid phase electrolyte.
[0059] In addition, the crosslinkable functional group (CFG) may be included in an amount of 10 wt% to 20 wt% based on the total weight of the polyhedral oligomeric silsesquioxane (CFG-POSS) containing the crosslinkable functional group. Specifically, the content of the crosslinkable functional group (CFG) may be 10 wt% or more, 11 wt% or more, or 12 wt% or less, or 18 wt% or less, 19 wt% or less, or 20 wt% or less. If the content of the crosslinkable functional group (CFG) is less than 10 wt%, crosslinks between the functional groups may not be sufficiently formed, making it difficult to form a solid electrolyte. If the content of the crosslinkable functional group (CFG) is more than 20 wt%, crosslinks between the functional groups may increase, ensuring strength, but the chain mobility of the polymer chain may decrease, decreasing ion conductivity.
[0060] In the present invention, the lithium salt is contained in a dissociated state in the internal space of the cross-linked structure, and can improve the ionic conductivity of the polymer solid electrolyte.
[0061] The lithium salt is (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 may contain one or more selected from the group consisting of:
[0062] The lithium salt may be contained in an amount of 5 wt% to 50 wt% based on the total weight of the polymer solid electrolyte, specifically, 5 wt% or more, 7 wt% or more, or 9 wt% or more, or 30 wt% or less, 40 wt% or less, or 50 wt% or less. If the content of the lithium salt is less than 5 wt%, the amount of dissociated lithium ions is small, and the ionic conductivity may be low, whereas if the content exceeds 50 wt%, the lithium salt may not be sufficiently dissociated, and the ionic conductivity may be low.
[0063] In the present invention, the polymer solid electrolyte may be in the form of a free-standing film or a coating layer. The free-standing film means a film that has a certain strength at room temperature and pressure and can maintain a film shape by itself without a separate support. The coating layer means a layer obtained by coating on a substrate.
[0064] The free-standing film or coating layer has a characteristic as a support that stably contains lithium ions, and is therefore a suitable form for a polymer solid electrolyte.
[0065] In the present invention, the polymer solid electrolyte may further include a liquid electrolyte, which can further improve the ionic conductivity of the polymer solid electrolyte. The liquid electrolyte may also be contained in the inner space of the cross-linked structure.
[0066] The liquid electrolyte may be a liquid electrolyte commonly used in the art, and the composition of the liquid electrolyte is not particularly limited as long as it can be used in a lithium secondary battery. For example, the liquid electrolyte may include a lithium salt and a non-aqueous solvent. The lithium salt may be any of the lithium salts described above. In addition, the non-aqueous solvent may include one or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane.
[0067] In addition, the liquid electrolyte may be included in an amount of 1 wt% to 5 wt% based on the total weight of the polymer solid electrolyte. If the content of the liquid electrolyte is 1 wt% or less, the effect of improving ion conductivity may be negligible, and if it exceeds 5 wt%, the stability may be reduced.
[0068] (2) Manufacturing method of polymer solid electrolyte (A) The present invention also relates to a method for producing a polymer solid electrolyte (A), the method for producing the polymer solid electrolyte comprising: (S1) adding a lithium salt to liquid-phase polyhedral oligomeric silsesquioxane (POSS) (CFG-POSS) containing a crosslinkable functional group to form a polymer solid electrolyte-forming solution; (S2) applying the polymer solid electrolyte-forming solution onto a substrate to form a coating film; and (S3) curing the coating film.
[0069] Hereinafter, each step of the method for preparing the solid electrolyte (A) according to the present invention will be described in more detail.
[0070] In the present invention, in step (S1), a lithium salt may be added to a liquid phase polyhedral oligomeric silsesquioxane (POSS) (CFG-POSS) containing a crosslinkable functional group (CFG) to form a polymer solid electrolyte forming solution. The type and content of the polyhedral oligomeric silsesquioxane (CFG-POSS) containing a crosslinkable functional group and the lithium salt are as described above.
[0071] A lithium salt can be added to the liquid phase polyhedral oligomeric silsesquioxane (CFG-POSS) containing crosslinkable functional groups, and the mixture is stirred to form a polymer solid electrolyte forming solution.
[0072] In addition, since the polyhedral oligomeric silsesquioxane containing a crosslinkable functional group (CFG-POSS) exists in a liquid phase at room temperature, a lithium salt may be added to the liquid-phase POSS to dissociate the lithium salt, or a solvent may be further added to increase the amount of lithium salt dissociated.
[0073] The solvent is not particularly limited as long as it can dissociate a lithium salt into the liquid-phase polyhedral oligomeric silsesquioxane (CFG-POSS) having a crosslinkable functional group. For example, the solvent may be at least one selected from the group consisting of dimethylsulfoxide (DMSO), isopropyl alcohol, N-Methyl-2-pyrrolidone (NMP), acetone, xylene, N,N-Dimethylmethanamide (DMF), benzene, tetrahydrofuran (THF) and water. The amount of the solvent used may be adjusted in consideration of the coating thickness of the coating layer, the physical properties of the solid electrolyte to be manufactured, and the like.
[0074] In the present invention, in the step (S2), the polymer solid electrolyte forming solution can be applied onto a substrate to form a coating film.
[0075] The substrate is not particularly limited as long as it can serve as a support on which the polymer solid electrolyte forming solution is applied. For example, the substrate may be SUS (stainless steel), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.
[0076] In addition, the coating method is not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.
[0077] In the present invention, the coating film may be cured in step (S3). The curing process may induce crosslinking between the crosslinkable functional groups to form a crosslinked structure.
[0078] The curing may be thermal curing or photocuring.
[0079] The heat curing may be a heat treatment at a temperature of 80° C. to 200° C. Specifically, the heat treatment temperature may be 80° C. or higher, 90° C. or higher, or 100° C. or higher, or 160° C. or lower, 180° C. or lower, or 200° C. or lower. If the heat treatment temperature is lower than 80° C., crosslinks may not be sufficiently formed, and if it exceeds 200° C., the polymer solid electrolyte may be excessively cured, resulting in a decrease in ion conductivity, or the formed film may be damaged by heat.
[0080] The photocuring may be performed using ultraviolet rays (UV) or an electron beam.
[0081] [Polymer solid electrolyte (B)] (1) Polymer solid electrolyte (B) The present invention relates to a polymer solid electrolyte (B).
[0082] The polymer solid electrolyte (B) according to the present invention comprises a polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG) (CFG-POSS); a liquid-phase polyhedral oligomeric silsesquioxane (POSS); and a lithium salt.
[0083] In addition, the polymer solid electrolyte has a cross-linked structure formed by cross-linking between the cross-linkable functional groups. The lithium salt may be present in a dissociated state in a free volume, which is an internal space of the cross-linked structure. The liquid phase polyhedral oligomeric silsesquioxane (POSS) may also be included in the free volume. The cross-linked structure improves safety by preventing leakage and volatilization, and at the same time, serves as a path for lithium ions to move, thereby improving ionic conductivity. In addition, the free volume can provide a space in which solid electrolyte chains can move, thereby improving ionic conductivity.
[0084] FIG. 2 is a schematic diagram showing the internal structure of the polymer solid electrolyte (B) according to one embodiment of the present invention. 2, the polymer solid electrolyte (1) has a cross-linked structure formed by cross-linking between functional groups contained in a polyhedral oligomeric silsesquioxane (CFG-POSS) (10) containing a cross-linkable functional group, and an internal space contained in the cross-linked structure. In this case, the internal space may refer to a free volume. A liquid phase polyhedral oligomeric silsesquioxane (POSS) (20) may be contained in the internal space, and a lithium salt (not shown) may be contained in a dissociated state in the internal space.
[0085] The crosslinkable functional group is not particularly limited as long as it has a property of forming a crosslink by a curing process using heat or light. For example, the crosslinkable functional group may include one or more selected from the group consisting of glycidyl, methacryl, allyl, and acrylo. The glycidyl may be more advantageous for a crosslinked structure by crosslinking because it has a stronger tendency to bond with each other during heat treatment and / or light treatment. Preferably, the crosslink may be a bond formed by thermal crosslinking of glycidyl.
[0086] The strength of the cross-linking may affect the degree to which the polymer chains contained in the polymer solid electrolyte can move. Therefore, if the cross-linking is not bonded with an appropriate strength to allow the polymer chains to move, the solid electrolyte membrane cannot exhibit high ion conductivity while maintaining its strength. If the strength of the cross-linking is too high, the polymer chains may not move smoothly and it may be difficult to secure space for ions to move, resulting in low ion conductivity. On the other hand, if the strength of the cross-linking is too low, the processability may be reduced during the manufacture of the all-solid-state battery, and leakage may occur.
[0087] In addition, the polyhedral oligomeric silsesquioxane (CFG-POSS) containing a crosslinkable functional group may be included in an amount of 20 wt% to 50 wt% based on the total weight of the polymer solid electrolyte, specifically, 20 wt% or more, 25 wt% or more, or 30 wt% or more, or 40 wt% or less, 45 wt% or less, or 50 wt% or less. If the content of the POSS is less than 20 wt%, a polymer solid electrolyte is not formed, and if it exceeds 50 wt%, the content of the lithium salt increases relatively, and ion conductivity may decrease.
[0088] In addition, the crosslinkable functional group (CFG) may be included in an amount of 10 wt% to 20 wt% based on the total weight of the polyhedral oligomeric silsesquioxane (CFG-POSS) containing the crosslinkable functional group. Specifically, the content of the crosslinkable functional group (CFG) may be 10 wt% or more, 11 wt% or more, or 12 wt% or less, or 18 wt% or less, 19 wt% or less, or 20 wt% or less. If the content of the crosslinkable functional group (CFG) is less than 10 wt%, crosslinks between the functional groups may not be sufficiently formed, making it difficult to form a solid electrolyte. If the content of the crosslinkable functional group (CFG) is more than 20 wt%, crosslinks between the functional groups may increase, ensuring strength, but the chain mobility of the polymer chain may decrease, decreasing ion conductivity.
[0089] In the present invention, the liquid phase polyhedral oligomeric silsesquioxane (POSS) may be represented by the following chemical formula 1:
[0090] [ka]
[0091] In the above Chemical Formula 1, R are the same or different and are each independently selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4:
[0092] [ka]
[0093] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.
[0094] In addition, in the above chemical formulas 1-1 to 1-4, L1 to L5 are C1 to C10 alkylene groups, R1 to R4 are hydrogen, a hydroxyl group, or a C1 to C30 alkyl group, and m and n are the same or different and each independently an integer of 0 to 10.
[0095] In addition, in the above formula 1, R is selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group.
[0096] In addition, the liquid phase polyhedral oligomeric silsesquioxane (POSS) may be contained in an amount of 20 wt% to 50 wt% based on the total weight of the polymer solid electrolyte, and specifically, the content of the POSS may be 20 wt% or more, 25 wt% or more, or 30 wt% or more, or 40 wt% or less, 45 wt% or less, or 50 wt% or less. If the content of the POSS is less than 20 wt%, the effect of improving ion conductivity may be insignificant, and if it exceeds 50 wt%, liquid leakage may occur.
[0097] The liquid-phase polyhedral oligomeric silsesquioxane (POSS) is not particularly limited in type as long as it does not harden during heat treatment and can improve the movement of polymer chains constituting the polymer solid electrolyte. For example, the POSS may be PEG-POSS.
[0098] In the present invention, the lithium salt is contained in a dissociated state in the internal space of the cross-linked structure, and can improve the ionic conductivity of the polymer solid electrolyte.
[0099] The lithium salt is (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 may contain one or more selected from the group consisting of:
[0100] The lithium salt may be contained in an amount of 10 wt% to 40 wt% based on the total weight of the polymer solid electrolyte, specifically, 10 wt% or more, 15 wt% or more, or 20 wt% or more, or 30 wt% or less, 35 wt% or less, or 40 wt% or less. If the content of the lithium salt is less than 10 wt%, the amount of dissociated lithium ions is small, and the ionic conductivity may be low, whereas if the content exceeds 40 wt%, the lithium salt may not be sufficiently dissociated, and the ionic conductivity may be low.
[0101] In the present invention, the weight ratio of the polyhedral oligomeric silsesquioxane containing a crosslinkable functional group to PEG-POSS may be 0.05:1 to 1.5:1. Specifically, the weight ratio may be 0.05:1 or more, 0.075:1 or more, or 0.1:1 or more, and may be 1: or less, 1.25:1 or less, or 1.5:1 or less. If the weight ratio is outside the above range, it may be difficult to form a solid electrolyte form or the ion conductivity may decrease.
[0102] In the present invention, the polymer solid electrolyte may be in the form of a free-standing film or a coating layer. The free-standing film means a film that has a certain strength at room temperature and pressure and can maintain a film shape by itself without a separate support. The coating layer means a layer obtained by coating on a substrate.
[0103] The free-standing film or coating layer has a characteristic as a support that stably contains lithium ions, and is therefore a suitable form for a polymer solid electrolyte.
[0104] In the present invention, the polymer solid electrolyte may further include a liquid electrolyte, which can further improve the ionic conductivity of the polymer solid electrolyte. The liquid electrolyte may also be contained in the inner space of the cross-linked structure.
[0105] The liquid electrolyte may be a liquid electrolyte commonly used in the art, and the composition of the liquid electrolyte is not particularly limited as long as it can be used in a lithium secondary battery. For example, the liquid electrolyte may include a lithium salt and a non-aqueous solvent. The lithium salt may be any of the lithium salts described above. In addition, the non-aqueous solvent may include one or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane.
[0106] In addition, the liquid electrolyte may be included in an amount of 1 wt% to 5 wt% based on the total weight of the polymer solid electrolyte. If the content of the liquid electrolyte is 1 wt% or less, the effect of improving ion conductivity may be negligible, and if it exceeds 5 wt%, the stability may be reduced.
[0107] (2) Manufacturing method of polymer solid electrolyte (B) The present invention also relates to a method for producing a polymer solid electrolyte (B), which includes the steps of: (S1) forming a first solution containing a polyhedral oligomeric silsesquioxane (POSS) (CFG-POSS) containing a crosslinkable functional group and a first lithium salt; (S2) forming a second solution containing a polyhedral oligomeric silsesquioxane (POSS) and a second lithium salt; (S3) mixing the first solution with the second solution to form a polymer solid electrolyte forming solution; (S4) applying the polymer solid electrolyte forming solution onto a substrate to form a coating film; and (S5) curing the coating film. The first lithium salt and the second lithium salt are arbitrarily divided to distinguish the lithium salts used in each step, and may be the same or different types of lithium salts. The lithium salt contained in the produced polymer solid electrolyte may include both the first lithium salt and the second lithium salt.
[0108] Hereinafter, each step of the method for preparing the polymer solid electrolyte (B) according to the present invention will be described in detail. The type and content of each raw material are as described above.
[0109] In the present invention, in the step (S1), a first solution containing polyhedral oligomeric silsesquioxane (POSS) (CFG-POSS) having a crosslinkable functional group and a first lithium salt can be formed.
[0110] The polyhedral oligomeric silsesquioxane containing a crosslinkable functional group (CFG-POSS) is in a liquid phase at room temperature, so it may be dissociated by adding a lithium salt, but a solvent may be further added to increase the amount of the lithium salt that dissociates.
[0111] The solvent is not particularly limited as long as it is a solvent capable of dissociating a lithium salt into a liquid-phase polyhedral oligomeric silsesquioxane having a crosslinkable functional group. For example, the organic solvent may be at least one selected from the group consisting of dimethylsulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, xylene, N,N-dimethylmethanamide (DMF), benzene, tetrahydrofuran (THF) and water. The amount of the solvent used may be adjusted in consideration of the thickness of the coating layer and the physical properties of the solid electrolyte to be manufactured.
[0112] In the present invention, in the step (S2), a second solution including polyhedral oligomeric silsesquioxane (POSS) and a second lithium salt may be formed.
[0113] The polyhedral oligomeric silsesquioxane is in a liquid phase at room temperature, and can be dissociated by adding a lithium salt.
[0114] In the present invention, in the step (S3), the first solution and the second solution can be mixed to form a polymer solid electrolyte forming solution.
[0115] In the present invention, in the step (S4), the polymer solid electrolyte forming solution can be applied onto a substrate to form a coating film.
[0116] The substrate is not particularly limited as long as it can serve as a support on which the polymer solid electrolyte forming solution is applied. For example, the substrate may be SUS (stainless steel), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.
[0117] In addition, the coating method is not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.
[0118] In the present invention, the coating film may be cured in the step (S3). The curing process may induce cross-linking between the cross-linkable functional groups (CFG) to form a cross-linked structure.
[0119] The curing may be thermal curing or photocuring.
[0120] The heat curing may be a heat treatment at a temperature of 80° C. to 200° C. Specifically, the heat treatment temperature may be 80° C. or higher, 90° C. or higher, or 100° C. or higher, or 160° C. or lower, 180° C. or lower, or 200° C. or lower. If the heat treatment temperature is lower than 80° C., crosslinks may not be sufficiently formed, and if it exceeds 200° C., the polymer solid electrolyte may be excessively cured, resulting in a decrease in ion conductivity, or the formed film may be damaged by heat.
[0121] The photocuring may be performed using ultraviolet rays (UV) or an electron beam.
[0122] [Polymer solid electrolyte (C)] (1) Polymer solid electrolyte (C) The present invention relates to a polymer solid electrolyte (C).
[0123] The polymer solid electrolyte (C) according to the present invention comprises a liquid phase polyhedral oligomeric silsesquioxane (POSS); a solid phase cross-linking agent; and a lithium salt.
[0124] The polymer solid electrolyte has a cross-linked structure formed by cross-linking between the cross-linking agents of the solid phase. The lithium salt may be present in a dissociated state in a free volume, which is an internal space of the cross-linked structure. The cross-linked structure improves safety by preventing leakage and volatilization, and at the same time, serves as a path for lithium ions to move, thereby improving ion conductivity. The liquid phase polyhedral oligomeric silsesquioxane (POSS) may also be included in the free volume. The cross-linked structure improves safety by preventing leakage and volatilization, and at the same time, serves as a path for lithium ions to move, thereby improving ion conductivity. The free volume may provide a space in which the solid electrolyte chains can move, thereby improving ion conductivity.
[0125] FIG. 3 is a schematic diagram showing the internal structure of the polymer solid electrolyte (C) according to one embodiment of the present invention.
[0126] 3, the polymer solid electrolyte (1) has a cross-linked structure formed by a solid-phase cross-linking agent (40) and an internal space contained in the cross-linked structure. In this case, the internal space may refer to a free volume. A liquid-phase polyhedral oligomeric silsesquioxane (POSS) (20) may be contained in the internal space, and a lithium salt (not shown) may be contained in a dissociated state in the internal space.
[0127] In the present invention, the solid-phase cross-linking agent may have a property of being initially in a liquid phase, but changing into a solid phase by forming cross-links through a curing step using heat or light.
[0128] For example, the cross-linking agent may include one or more oligomers selected from the group consisting of polyethylene glycol diacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), and polyethylene glycol divinyl ether (PEGDVE). The solid-phase cross-linking agents may have a stronger tendency to bond to each other upon heat treatment and / or light treatment, which may be more advantageous for the formation of a cross-linked structure through cross-linking. The cross-linking may also refer to a physical bond between the solid-phase cross-linking agents.
[0129] In addition, the solid-phase cross-linking agent may be included in an amount of 20 wt% to 60 wt% based on the total weight of the polymer solid electrolyte, specifically, 20 wt% or more, 25 wt% or more, or 30 wt% or more, or 50 wt% or less, 55 wt% or less, or 60 wt% or less. If the content of the solid-phase cross-linking agent is less than 20 wt%, a cross-linked structure cannot be formed, and if it exceeds 60 wt%, the cross-linked structure becomes too large, blocking the ion migration path, which may reduce ion conductivity.
[0130] In the present invention, the liquid phase polyhedral oligomeric silsesquioxane (POSS) may be represented by the following chemical formula 1:
[0131] [ka]
[0132] In the above Chemical Formula 1, R are the same or different and are each independently selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4:
[0133] [ka]
[0134] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.
[0135] In addition, in the above chemical formulas 1-1 to 1-4, L1 to L5 are C1 to C10 alkylene groups, R1 to R4 are hydrogen, a hydroxyl group, or a C1 to C30 alkyl group, and m and n are the same or different and each independently an integer of 0 to 10.
[0136] In addition, in the above formula 1, R is selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group.
[0137] Preferably, the liquid-phase polyhedral oligomeric silsesquioxane (POSS) may be a liquid-phase polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) in which R in Chemical Formula 1 is a polyethylene glycol group (polyethylene glycol, PEG).
[0138] In addition, the liquid phase polyhedral oligomeric silsesquioxane (POSS) may be contained in an amount of 20% by weight to 60% by weight based on the total weight of the polymer solid electrolyte, and specifically, the content of the liquid phase polyhedral oligomeric silsesquioxane may be 20% by weight or more, 25% by weight or more, or 30% by weight or more, or 50% by weight or less, 55% by weight or less, or 60% by weight or less. If the content of the liquid phase polyhedral oligomeric silsesquioxane is less than 20% by weight, the effect of improving ion conductivity may be insignificant, and if it exceeds 60% by weight, there may be a problem that the strength of the solid electrolyte membrane cannot be maintained or liquid leakage may occur.
[0139] In the present invention, the lithium salt is contained in a dissociated state in the internal space of the cross-linked structure, and can improve the ionic conductivity of the polymer solid electrolyte.
[0140] The lithium salt is (CF 3 SO 2 ) 2NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 may contain one or more selected from the group consisting of:
[0141] The lithium salt may be contained in an amount of 10 wt% to 30 wt% based on the total weight of the polymer solid electrolyte, and specifically, the content of the lithium salt may be 10 wt% or more, 13 wt% or more, or 15 wt% or more, or 25 wt% or less, 28 wt% or less, or 30 wt% or less. If the content of the lithium salt is less than 10 wt%, the amount of dissociated lithium ions is small, and ionic conductivity may decrease, whereas if the content of the lithium salt is more than 30 wt%, the lithium salt may not be dissociated into pure components, and ionic conductivity may decrease.
[0142] In the present invention, the polymer solid electrolyte may be in the form of a free-standing film or a coating layer. The free-standing film means a film that has a certain strength at room temperature and pressure and can maintain a film shape by itself without a separate support. The coating layer means a layer obtained by coating on a substrate.
[0143] The free-standing film or coating layer has a characteristic as a support that stably contains lithium ions, and is therefore a suitable form for a polymer solid electrolyte.
[0144] In the present invention, the polymer solid electrolyte may further include a liquid electrolyte, which can further improve the ionic conductivity of the polymer solid electrolyte. The liquid electrolyte may also be contained in the inner space of the cross-linked structure.
[0145] The liquid electrolyte may be a liquid electrolyte commonly used in the art, and the composition of the liquid electrolyte is not particularly limited as long as it can be used in a lithium secondary battery. For example, the liquid electrolyte may include a lithium salt and a non-aqueous solvent. The lithium salt may be any of the lithium salts described above. In addition, the non-aqueous solvent may include one or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane.
[0146] In addition, the liquid electrolyte may be included in an amount of 1 wt% to 5 wt% based on the total weight of the polymer solid electrolyte. If the content of the liquid electrolyte is 1 wt% or less, the effect of improving ion conductivity may be negligible, and if it exceeds 5 wt%, the stability may be reduced.
[0147] (2) Manufacturing method of polymer solid electrolyte (C) The present invention also relates to a method for producing a polymer solid electrolyte (C), the method including: (S1) forming a polymer solid electrolyte-forming solution containing a liquid-phase polyhedral oligomeric silsesquioxane (POSS), a cross-linking agent, and a lithium salt; (S2) applying the polymer solid electrolyte-forming solution onto a substrate to form a coating film; and (S3) curing the coating film.
[0148] Hereinafter, each step of the method for preparing the polymer solid electrolyte (C) according to the present invention will be described in more detail.
[0149] In the present invention, in the step (S1), a solution for forming a polymer solid electrolyte may be formed, which includes a liquid polyhedral oligomeric silsesquioxane (POSS), a cross-linking agent, and a lithium salt. The types and contents of the polyhedral oligomeric silsesquioxane, the cross-linking agent, and the lithium salt are as described above.
[0150] The polyhedral oligomeric silsesquioxane (POSS) is in a liquid phase, and a solution for forming a polymer solid electrolyte can be formed by adding a lithium salt to the liquid polyhedral oligomeric silsesquioxane to dissociate it, and then adding a cross-linking agent to the liquid polyhedral oligomeric silsesquioxane. At this time, the cross-linking agent is in a liquid phase and has a property of changing into a solid phase by forming cross-links through a curing process described below.
[0151] In the present invention, in the step (S2), the polymer solid electrolyte forming solution can be applied onto a substrate to form a coating film.
[0152] The substrate is not particularly limited as long as it can serve as a support on which the polymer solid electrolyte forming solution is applied. For example, the substrate may be SUS (stainless steel), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.
[0153] In addition, the coating method is not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.
[0154] In the present invention, the coating film can be cured in the step (S3). The curing process induces cross-linking between the cross-linking agents, and the cross-linking agents become solid, forming a cross-linked structure consisting of cross-linking between the cross-linking agents in the solid phase.
[0155] The curing may be thermal curing or photocuring.
[0156] The heat curing may be a heat treatment at a temperature of 80° C. to 200° C. Specifically, the heat treatment temperature may be 80° C. or higher, 90° C. or higher, or 100° C. or higher, or 160° C. or lower, 180° C. or lower, or 200° C. or lower. If the heat treatment temperature is lower than 80° C., crosslinks may not be sufficiently formed, and if it exceeds 200° C., the polymer solid electrolyte may be excessively cured, resulting in a decrease in ion conductivity, or the formed film may be damaged by heat.
[0157] The photocuring may be performed using ultraviolet rays (UV) or an electron beam.
[0158] all solid state battery The present invention also relates to an all-solid-state battery comprising the polymer solid electrolyte, the all-solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, and at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer may comprise the polymer solid electrolyte.
[0159] When the positive electrode layer includes a polymer solid electrolyte, the polymer solid electrolyte may be formed on one side of the positive electrode active material layer. When the negative electrode layer includes a polymer solid electrolyte, the polymer solid electrolyte may be formed on one side of the negative electrode active material layer. When the positive electrode layer and / or the negative electrode layer includes a polymer solid electrolyte, the ionic conductivity of the positive electrode and the negative electrode can be improved.
[0160] In addition, the polymer solid electrolyte may function as an adhesive in the positive electrode and / or negative electrode. An additional layer may be formed on the polymer solid electrolyte that functions as an adhesive. For example, a protective layer for protecting the positive electrode and the negative electrode may be formed by being bonded to each other by the polymer solid electrolyte.
[0161] Furthermore, when the solid electrolyte layer contains the polymer solid electrolyte, it can function as an electrolyte by itself.
[0162] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0163] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0164] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Li[Ni x Co y Mn z M v ]O 2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals; 1+y Mn 2-y O 4 (where y is 0 to 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxides such as lithium copper oxide (Li2 CuO 2 LiV 3 O 8 , Life 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-y MyO 2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); 2-y M y O 2 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li 2 Mn 3 MO 8 Lithium manganese oxides represented by the formula LiMn (where M is Fe, Co, Ni, Cu or Zn); 2 O 4 ;Disulfide compounds;Fe 2 (MoO 4 ) 3 These include, but are not limited to:
[0165] In addition, the positive electrode active material may be included in an amount of 40 wt% to 80 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 wt% or more or 50 wt% or more, and 70 wt% or less or 80 wt% or less. If the content of the positive electrode active material is less than 40 wt%, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt%, the mass transfer resistance may be large.
[0166] The binder is a component that assists in binding the positive electrode active material to the conductive material and the like and binding to the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polybutadiene ... The binder may include one or more selected from the group consisting of lylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include one or more selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0167] The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 1 wt% or more or 3 wt% or more, and 15 wt% or less or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.
[0168] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Typically, graphite or conductive carbon may be used. For example, graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; may be used alone or in a mixture of two or more kinds, but are not necessarily limited to these.
[0169] The conductive material may be contained in an amount of 0.5 wt% to 30 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the conductive material may be 0.5 wt% or more or 1 wt% or more, and 20 wt% or less or 30 wt% or less. If the content of the conductive material is less than 0.5 wt%, the effect of improving electrical conductivity may be difficult to expect, or the electrochemical properties of the battery may be deteriorated, and if the content is more than 30 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. There is no particular limit to the method of incorporating the conductive material into the positive electrode, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.
[0170] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0171] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0172] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may have various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.
[0173] The positive electrode may be manufactured according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.
[0174] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0175] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversible intercalation or deintercalation of lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.
[0176] The lithium ion (Li +The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0177] Preferably, the negative electrode active material is lithium metal, and more particularly, may be in the form of a lithium metal thin film or lithium metal powder.
[0178] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0179] The binder is the same as that described above in the positive electrode active material layer.
[0180] The conductive material is the same as that described above in the positive electrode active material layer.
[0181] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with fine irregularities formed on the surface.
[0182] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a layer or film forming method commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0183] Battery Module The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0184] In this case, specific examples of the device include, but are not limited to, power tools that are powered by a battery-type motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0185] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0186] [Examples 1 to 3 and Comparative Examples 1 to 4] In the following Examples 1 to 3 and Comparative Examples 1 to 4, polymer solid electrolytes (A) were produced according to the compositions shown in Table 1 below.
[0187] [Table 1]
[0188] Example 1 A solution for forming a polymer solid electrolyte was obtained by adding a lithium salt LiTFSI to a liquid phase polyhedral oligomeric silsesquioxane (Glycidyl-POSS) containing a crosslinkable functional group glycidyl, and thoroughly stirring for 12 hours. At this time, a solvent NMP (N-Methyl-2-pyrrolidone) was further added so that the Glycidyl-POSS and LiTFSI could be mixed well. The weight ratio of the Glycidyl-POSS and LiTFSI was set to 1:0.1.
[0189] The polymer solid electrolyte forming solution was applied onto a SUS foil with a doctor blade to form a coating film.
[0190] Thereafter, the mixture was heat-treated at 130° C. for one day, and then dried at the same time as being thermally cured to produce a membrane-like polymer solid electrolyte.
[0191] Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of POSS containing a crosslinkable functional group to the lithium salt (Glycidyl-POSS to LiTFSI) was 1:0.4.
[0192] Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that polyhedral oligomeric silsesquioxane (Acrylo-POSS) containing an acrylo group, which is a crosslinkable functional group, was used and the weight ratio of the Acrylo-POSS to LiTFSI was 1:0.4.
[0193] Comparative Example 1 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that polyhedral oligomeric silsesquioxane containing polyethylene glycol (PEG-POSS) was used instead of Glycidyl-POSS.
[0194] Comparative Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 2, except that heat treatment was not performed and vacuum drying was performed at 80° C. to dry the solvent NMP.
[0195] Comparative Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 2, except that polyhedral oligomeric silsesquioxane (Methacryl-POSS) containing a non-crosslinkable functional group, methacryl, was used instead of Glycidyl-POSS.
[0196] Comparative Example 4 A polymer solid electrolyte was prepared in the same manner as in Example 2, except that polyhedral oligomeric silsesquioxane containing an allyl group, which is a non-crosslinkable functional group (Allyl-POSS), was used instead of Glycidyl-POSS.
[0197] Experimental Example 1: Evaluation of the physical properties of polymer solid electrolyte (A) The polymer solid electrolytes produced in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to tests for ion conductivity and membrane state as described below, and the results are shown in Table 2 below.
[0198] (1) Ionic conductivity 1.7671cm 2 The solid polymer electrolyte was punched out into a circle of the same size, and the punched solid polymer electrolyte was placed between two pieces of stainless steel (SS) to manufacture a coin cell. An AC voltage was applied to the coin cell at room temperature, and the application conditions were set to a measurement frequency in the amplitude range of 500KHz to 20MHz, and the impedance was measured using a VMP3 manufactured by BioLogic. Using the following formula 1, the resistance (Rb) of the solid polymer electrolyte was calculated from the intersection point where the semicircle or straight line of the measured impedance locus intersected with the actual contraction, and the ionic conductivity (σ) was calculated from the area (A) and thickness (t) of the solid polymer electrolyte.
[0199]
number
[0200] σ: Ionic conductivity of polymer solid electrolyte Rb:Resistance A: Size of polymer solid electrolyte t: Thickness of the polymer solid electrolyte
[0201] (2) Membrane state The state of the polymer solid electrolyte membrane was observed with the naked eye to judge whether or not it was formed into a film.
[0202] [Table 2]
[0203] As shown in Table 2, when liquid-phase POSS containing a cross-linkable functional group and a lithium salt are used as raw materials and heat-treated, a solid-phase membrane having improved ionic conductivity is produced.
[0204] [Examples 4 to 10 and Comparative Examples 5 to 9] In the following Examples 4 to 10 and Comparative Examples 5 to 9, polymer solid electrolytes (B) were produced according to the compositions shown in Table 3 below.
[0205] [Table 3]
[0206] Example 4 (1) Preparation of solution for forming polymer solid electrolyte The liquid phase PEG-POSS was homogeneously mixed with a lithium salt, LiTFSI, in a weight ratio of 1:0.4 and dissociated to prepare a first solution.
[0207] A liquid phase polyhedral oligomeric silsesquioxane (GL-POSS) containing glycidyl (GL), a crosslinkable functional group, was mixed with a lithium salt LiTFSI at a weight ratio of 1:0.4 and dissociated. A second solution was prepared by adding the same amount of NMP as the GL-POSS.
[0208] The first solution and the second solution were uniformly mixed so that the weight ratio of the PEG-POSS and the GL-POSS was 1:1, to prepare a polymer solid electrolyte forming solution.
[0209] (2) Production of polymer solid electrolytes The polymer solid electrolyte forming solution was applied onto a SUS foil with a doctor blade to form a coating film.
[0210] Thereafter, the mixture was heat-treated at 130° C. for 1 day and dried in vacuum to produce a polymer solid electrolyte.
[0211] Example 5 A polymer solid electrolyte was prepared in the same manner as in Example 4, except that the weight ratio of the PEG-POSS and GL-POSS was 1:0.25.
[0212] Example 6 A polymer solid electrolyte was prepared in the same manner as in Example 4, except that MA-POSS (methacryl-POSS) was used instead of GL-POSS, and the weight ratio of PEG-POSS to MA-POSS was 1:0.1.
[0213] Example 7 A polymer solid electrolyte was prepared in the same manner as in Example 6, except that the weight ratio of PEG-POSS to MA-POSS was 1:0.2.
[0214] Example 8 A polymer solid electrolyte was prepared in the same manner as in Example 6, except that the weight ratio of PEG-POSS to MA-POSS was 1:0.3.
[0215] Example 9 A polymer solid electrolyte was prepared in the same manner as in Example 4, except that AL-POSS (allyl-POSS) was used instead of GL-POSS, and the weight ratio of PEG-POSS to AL-POSS was 1:0.2.
[0216] Example 10 A polymer solid electrolyte was prepared in the same manner as in Example 4, except that AC-POSS (acrylo-POSS) was used instead of GL-POSS, and the weight ratio of PEG-POSS to AC-POSS was 1:0.2.
[0217] Comparative Example 5 Without using GL-POSS, PEG-POSS and LiTFSI were mixed in a weight ratio of 1:0.4, and the same procedure as in Example 4 was carried out without heat treatment.
[0218] Comparative Example 6 The same procedure as in Comparative Example 5 was carried out except that the heat treatment was performed at 130° C. for 1 day and vacuum drying.
[0219] Comparative Example 7 The second solution prepared in Example 4 was applied onto a SUS foil with a doctor blade to form a coating film. No heat treatment was performed.
[0220] Comparative Example 8 The same procedure as in Example 4 was carried out, except that the weight ratio of the PEG-POSS to the GL-POSS was 1:0.025.
[0221] Comparative Example 9 The second solution was prepared in the same manner as in Example 4, except that only the second solution was prepared using MA-POSS instead of GL-POSS, and then a coating film was formed only from the second solution, followed by heat treatment.
[0222] Experimental Example 2: Evaluation of the physical properties of polymer solid electrolyte (B) For the polymer solid electrolytes produced in Examples 4 to 10 and Comparative Examples 4 to 9, tests were carried out on the ion conductivity and membrane state in the same manner as in Experimental Example 1, and the results are shown in Table 4 below.
[0223] [Table 4]
[0224] As shown in Table 4 above, in Examples 4 to 10, solid electrolytes were produced and the ionic conductivity was excellent.
[0225] On the other hand, in Comparative Examples 5 and 6, a liquid phase electrolyte was produced without using a POSS containing a cross-linkable functional group.
[0226] In Comparative Example 7, GL-POSS containing glycidyl (GL), a cross-linking functional group, was used, but no heat treatment was performed, and a liquid phase electrolyte was produced. In Comparative Example 8, PEG-POSS and GL-POSS were used as raw materials in the same manner as in Example 1, but the amount of GL-POSS used was too small, and a liquid phase electrolyte was produced.
[0227] In addition, in Comparative Example 9, a solid electrolyte was produced, but PEG-POSS was not used, and it was found that the ionic conductivity was reduced.
[0228] [Examples 11 to 14 and Comparative Examples 10 to 12] In the following Examples 11 to 14 and Comparative Examples 10 to 12, polymer solid electrolytes (C) were produced according to the compositions shown in Table 5 below.
[0229] [Table 5]
[0230] Example 11 Liquid phase polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) and lithium salt LiTFSI were uniformly mixed in a weight ratio of 1:0.4, and LiTFSI was dissociated. Then, PEGDMA (poly(ethylene glycol) dimethacrylate), a cross-linking agent, was further mixed to obtain a polymer solid electrolyte forming solution. At this time, the weight ratio of the PEG-POSS to PEGDMA was set to 1:1.
[0231] The polymer solid electrolyte forming solution was applied onto a SUS foil with a doctor blade to form a coating film.
[0232] Thereafter, the resultant was heat-treated at 100° C. for one day to produce a membrane-shaped polymer solid electrolyte membrane.
[0233] Example 12 A polymer solid electrolyte membrane was prepared in the same manner as in Example 11, except that the weight ratio of PEG-POSS / LiTFSI to PEGDMA was 1:2.
[0234] Example 13 A polymer solid electrolyte membrane was prepared in the same manner as in Example 11, except that PEGDA (Poly(ethylene glycol) diacrylate) was used instead of PEGDMA as a cross-linking agent.
[0235] Example 14 A polymer solid electrolyte membrane was prepared in the same manner as in Example 11, except that PEGDVE (poly(ethylene glycol) divinyl ether) was used instead of PEGDMA as a cross-linking agent.
[0236] Comparative Example 10 The same procedure as in Example 11 was carried out, except that no cross-linking agent was used and no heat treatment was performed.
[0237] Comparative Example 11 A polymer solid electrolyte was prepared in the same manner as in Example 11, except that no cross-linking agent was used.
[0238] Comparative Example 12 A polymer solid electrolyte was prepared in the same manner as in Example 11, except that PEG-POSS was not used.
[0239] Experimental Example 3: Evaluation of the physical properties of polymer solid electrolyte (C) The polymer solid electrolytes prepared in the Examples and Comparative Examples were tested for ion conductivity and membrane state in the same manner as in Experimental Example 1, and the results are shown in Table 6 below.
[0240] [Table 6]
[0241] As shown in Table 6, in Examples 11 to 14, the polymer solid electrolytes were prepared by heat treatment using a cross-linking agent together with PEG-POSS. All of the polymer solid electrolytes were in the form of solid membranes and had excellent ionic conductivity.
[0242] In Comparative Examples 10 and 11, no solid-phase cross-linking agent was used and a liquid-phase electrolyte was produced.
[0243] In Comparative Example 12, a solid-phase membrane electrolyte was prepared using a solid-phase cross-linking agent without using PEG-POSS, but the ion conductivity was poor.
[0244] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it is obvious that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below. [Explanation of symbols]
[0245] 1: Polymer solid electrolyte 10: Polyhedral oligomeric silsesquioxanes containing cross-linkable functional groups (CFG-POSS) 20: Liquid-phase polyhedral oligomeric silsesquioxanes (POSS) 30: Lithium salt 40: Solid-phase cross-linking agent
Claims
1. A polymer solid electrolyte comprising the following (A), (B) or (C): The polymer solid electrolyte containing (A) or (B) has a cross-linked structure formed by cross-linking between the cross-linkable functional groups, The polymer solid electrolyte containing (C) has a cross-linked structure formed by a solid-phase cross-linking agent. (A) a polyhedral oligomeric silsesquioxane (POSS) containing a crosslinkable functional group (CFG), and a lithium salt; (B) polyhedral oligomeric silsesquioxane (POSS) containing crosslinkable functional groups (CFG) (CFG-POSS); liquid-phase polyhedral oligomeric silsesquioxane (POSS); and a lithium salt; and (C) Liquid phase polyhedral oligomeric silsesquioxane (POSS); solid phase cross-linking agent, and lithium salt.
2. 2. The polymer solid electrolyte according to claim 1, wherein the crosslinkable functional group of (A) includes at least one selected from the group consisting of glycidyl (GL) and acrylo (AC).
3. The polymer solid electrolyte according to claim 1, wherein the polyhedral oligomeric silsesquioxane having a crosslinkable functional group (A) is contained in an amount of 50 wt % to 95 wt % based on the total weight of the polymer solid electrolyte.
4. 2. The polymer solid electrolyte according to claim 1, wherein the lithium salt (A) is contained in an amount of 5 to 50 wt % based on the total weight of the polymer solid electrolyte.
5. 2. The polymer solid electrolyte according to claim 1, wherein the crosslinkable functional group (CFG) of (B) includes at least one selected from the group consisting of glycidyl (GL), acrylo (AC), allyl (AL) and methacryl (MA).
6. The polymer solid electrolyte according to claim 1, wherein the weight ratio (CFG-POSS:POSS) of the polyhedral oligomeric silsesquioxane (B) containing a crosslinkable functional group (CFG-POSS) to the polyhedral oligomeric silsesquioxane (POSS) is 0.05:1 to 1.5:
1.
7. 2. The polymer solid electrolyte according to claim 1, wherein the (B) polyhedral oligomeric silsesquioxane (CFG-POSS) having a crosslinkable functional group is contained in an amount of 20 wt % to 50 wt % based on the total weight of the polymer solid electrolyte.
8. 2. The polymer solid electrolyte according to claim 1, wherein the polyhedral oligomeric silsesquioxane (POSS) of (B) is contained in an amount of 20 wt % to 50 wt % based on the total weight of the polymer solid electrolyte.
9. 2. The polymer solid electrolyte according to claim 1, wherein the lithium salt (B) is contained in an amount of 10 to 40 wt % based on the total weight of the polymer solid electrolyte.
10. 2. The polymer solid electrolyte according to claim 1, wherein the solid-phase cross-linking agent (C) comprises at least one selected from the group consisting of polyethylene glycol diacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), and polyethylene glycol divinyl ether (PEGDVE).
11. 2. The polymer solid electrolyte according to claim 1, wherein the liquid phase polyhedral oligomeric silsesquioxane (POSS) of (C) is contained in an amount of 20 wt % to 60 wt % based on the total weight of the polymer solid electrolyte.
12. 2. The polymer solid electrolyte according to claim 1, wherein the solid phase cross-linking agent (C) is contained in an amount of 20 to 60 wt % based on the total weight of the polymer solid electrolyte.
13. 2. The polymer solid electrolyte according to claim 1, wherein the lithium salt (C) is contained in an amount of 10 to 30 wt % based on the total weight of the polymer solid electrolyte.
14. The polymer solid electrolyte according to claim 1 , wherein the polymer solid electrolyte is in the form of a freestanding film.
15. The polymer solid electrolyte according to claim 1 , further comprising a liquid electrolyte.
16. An all-solid-state battery comprising the polymer solid electrolyte according to any one of claims 1 to 15.
17. The all-solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, 17. The all-solid-state battery according to claim 16, wherein at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer contains the polymer solid electrolyte.
18. A battery module comprising the all-solid-state battery according to claim 17.
Citation Information
Patent Citations
Hybrid polymer electrolyte as well as preparation method and application thereof
CN110994013A
Electrolyte for secondary battery
JP2020076024A
Organic-inorganic hybrid block or random copolymer and polymer electrolyte for lithium secondary battery using the same and lithium secondary battery
KR101232607B1
Hybrid Electrolytes with Controlled Network Structures for Lithium Metal Batteries
US20180226679A1
KR2017-0046995